2021
DOI: 10.1021/acsaem.1c00665
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Performances by Wet Ball Milling to Introduce Structural Water into an Electrolytic MnO2/Graphite Nanocomposite Cathode for Zinc-Ion Batteries

Abstract: The introduction of structural water in cathode materials of zinc-ion batteries can reduce electrostatic interactions to promote zinc-ion diffusion. However, it is difficult to introduce structural water in MnO 2 cathodes due to annealing for crystallinity. For the first time, we introduce structural water into MnO 2 /graphite nanocomposites by simple wet ball milling of a mixture of electrolytic MnO 2 and natural graphite. The composites of nanorod MnO 2 /graphite exhibit a high discharge capacity (312 mA h g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Low stirring speed and suitable heating temperature made single-atom Pt uniformly anchored on MnO 2 loaded on carbon cloth during the process of electrochemical deposition. Wet ball milling could achieve the nanocrystallization of Pt-MnO 2 and made its particles finer and more uniform, which could improve the electrochemical performance of electrode materials. , XRD patterns in Figure b illustrate that the peaks at 12.5°, 25.2°, 37.3°, and 65.6° are indexed to the (0 0 1), (0 0 2), (−1 1 1), and (0 2 0) planes of δ-MnO 2 , respectively, with a space group of C 2/ m (JCPDS no. 80-1098).…”
Section: Resultsmentioning
confidence: 99%
“…Low stirring speed and suitable heating temperature made single-atom Pt uniformly anchored on MnO 2 loaded on carbon cloth during the process of electrochemical deposition. Wet ball milling could achieve the nanocrystallization of Pt-MnO 2 and made its particles finer and more uniform, which could improve the electrochemical performance of electrode materials. , XRD patterns in Figure b illustrate that the peaks at 12.5°, 25.2°, 37.3°, and 65.6° are indexed to the (0 0 1), (0 0 2), (−1 1 1), and (0 2 0) planes of δ-MnO 2 , respectively, with a space group of C 2/ m (JCPDS no. 80-1098).…”
Section: Resultsmentioning
confidence: 99%
“…The pyrolusite-type β-MnO 2 ( P 42/ mnm ) has a rutile-type structure with infinite [MnO 6 ] octahedral chains that share opposing edges. Each chain is connected with four similar chain corners, leading to the formation of (1 × 1) tunnels in this structure. The structural feature of γ-MnO 2 is the random intergrowth of ramsdellite-type (1 × 2 tunnels) and pyrolusite (1 × 1 tunnels) matrices, where the basic building blocks of [MnO 6 ] octahedra share the corners and edges. , The structure of birnessite-type δ-MnO 2 consists of [MnO 6 ] octahedral sheets that share edges, forming a two-dimensional (2D) layer structure with the interlayers filled with K + OH – or H 2 O. , The structure of akhtenskite-type ε-MnO 2 is a polymorph of MnO 2 with a hexagonal symmetry, first discovered by De Wolff et al It exhibits a NiAs-type structure with half cationʼs vacancies and Mn 4+ randomly distributed. , However, the ordered structure of ε-MnO 2 and the DFT calculations have also been proposed and performed in recent years, respectively. Hong and co-authors revealed a ε-MnO 2 material by acid leaching of LiMnO x . The formation energies of oxygen vacancies were calculated based on both bulk and surface ε-MnO 2 by DFT calculations .…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that doping Fe could greatly increase the oxygen vacancy concentration of ε-MnO 2 , thereby improving the toluene oxidation activity. Zhang and co-authors also calculated the adsorption energies of H 2 O for the ε-MnO 2 planes (102) and (110) . In this paper, we established a reliable unit cell model according to the space group ( P 63/ mmc , #194) of ε-MnO 2 and the unit cell parameters ( a = b = 0.2786 nm, c = 0.4412 nm, α = β = 90°, γ = 120°).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the higher ionic conductivity (∼1 S cm −1 ) in aqueous electrolytes enables a superior power density compared to non-aqueous systems. 7 To date, various materials suitable for reversible Zn 2+ insertion/extraction have been investigated as cathodes for ZIBs, mainly including manganese-based composites, vanadium-based composites, and Prussian blue analogues, [8][9][10][11][12][13][14][15][16][17][18][19] among which vanadium pentoxide (V 2 O 5 ) has attracted widespread attention owing to its multiple valence states and thus remarkable theoretical capacity of 589 mA h g −1 for Zn 2+ storage (based on a two-electron transfer process). [20][21][22][23][24][25][26][27][28][29] Nevertheless, the poor intrinsic conductivity and the sluggish ion diffusion kinetics caused by the narrow layer spacing in the V 2 O 5 framework result in inferior rate capability and unsatisfactory cycling performances.…”
Section: Introductionmentioning
confidence: 99%